Concept analysis of maternal-infant attachment during the weaning process - Artemio M. Gonzales Jr; Lourdes Marie S. Tejero (Belitung Nursing Journal, 2022)
Background: At the time that the mother and baby transit from breastfeeding to weaning, maternal-fetal attachment becomes a crucial basis for maintaining their emotional relationship. Conceptualization is needed to better understand the phenomenon of maternal-infant attachment during the weaning process. Objective: The purpose of this paper is to explore and identify the essence of the term maternal-infant attachment during weaning and to arrive at an operational definition of the concept. Method: Concept analysis following Walker and Avant. Results: The attributes of maternal-infant attachment during the weaning process include (1) consistent and properly timed, (2) dynamic transactional interaction, and (3) secured adjustment. Maternal-infant attachment during the weaning process is brought by maternal sensitivity, closeness and proximity seeking, gentle and positive weaning, and breastfeeding experiences, which later turn into favorable emotion regulation, maturity, self-efficacy, secured bond, less intrusive interaction, resilience, and child’s behavioral and development. Conclusion: This concept analysis provides new insight into maternal-infant attachment during the weaning process that guides the nursing practice. Also, the findings can help develop or improve the models, theories, and instruments collected for maintaining maternal-fetal attachment during the weaning process.